2009 International Conference on Machine Learning and Cybernetics 2009
DOI: 10.1109/icmlc.2009.5212718
|View full text |Cite
|
Sign up to set email alerts
|

Comparing background elimination approaches for processing of ancient Thai manuscipts on palm leaves

Abstract: Abstract:The objective of the Preservation of Palm Leaf Manuscripts Project at Mahasarakham University at Thailand is to preserve and retrieve traditional knowledge from ancient manuscripts recorded on palm leaves. An essential task in the process is to recognize the ancient characters automatically through image processing techniques. The paper compares different background elimination approaches which could be used. The aim is to improve the global and local adaptive thresholding techniques intelligently, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…Some of those algorithms are more efficient in specific documents. On the other hand, in the authors' pervious paper [1], it was demonstrated that when the thresholding techniques was applied to evaluate ancient Thai manuscripts on palm leaves, no single method could be claimed to give an optimal result for all images. In addition, most decisions on how to choose these algorithms were subjectively decided by human.…”
Section: ) Object Attribute-based Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Some of those algorithms are more efficient in specific documents. On the other hand, in the authors' pervious paper [1], it was demonstrated that when the thresholding techniques was applied to evaluate ancient Thai manuscripts on palm leaves, no single method could be claimed to give an optimal result for all images. In addition, most decisions on how to choose these algorithms were subjectively decided by human.…”
Section: ) Object Attribute-based Methodsmentioning
confidence: 99%
“…The pixels are separated into two classes: foreground and background. This can be expressed as follows [1] …”
Section: Binarization Techniquesmentioning
confidence: 99%
See 2 more Smart Citations
“…Several binarization algorithms have been proposed in the literature [4][5][6][7][8][9][10][11][12][13]. However, it is difficult to select the optimal algorithm.…”
Section: Introductionmentioning
confidence: 99%